Green brine-free talc-based flame retardant and preparation method thereof
By adding modified composite materials in the preparation process of hydrotalcite, the dispersion of hydrotalcite in polymer is improved, and the problems of poor dispersion and limited flame retardant properties of hydrotalcite-based flame retardant are solved, thereby achieving higher flame retardant performance and smoke suppression effects.
Patent Information
- Application Number
- CN202411995949.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing hydrotalcite-based flame retardants have poor dispersion in polymers, resulting in limited flame retardant performance and are prone to accumulation and affect performance.
By adding modified composite materials, including γ-chloropropyltriethoxysilane, graphene and diatomaceous earth, and using ultrasonic dispersion, constant temperature stirring and dropping methods, the dispersion and flame retardant properties of hydrotalcite are improved.
The dispersion and flame retardant properties of hydrotalcite in polymers are significantly improved, the flame retardant grade and ultimate oxygen index of the polymers are enhanced, and the effects of suppressing smoke and purifying air are good.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flame retardants, and particularly relates to a green halogen-free hydrotalcite-based flame retardant and a preparation method thereof. Background Art
[0002] Flame retardants refer to functional additives that make flammable polymers flame retardant. They are mainly designed for the flame retardancy of polymer materials. According to the method of use, they are divided into additive flame retardants and reactive flame retardants. Among them, additive flame retardants are added to polymers by mechanical mixing to make them flame retardant. They have a wide range of applications. At present, additive flame retardants mainly include organic flame retardants and inorganic flame retardants, halogen flame retardants (organic chlorides and organic bromides) and non-halogen flame retardants.
[0003] In recent years, with the rapid development of materials science, the total volume output of polymer materials represented by plastics, rubber, fiber and coatings has exceeded the output of all metals, and the development and research of corresponding fire retardant coatings are very active. Through research, people have found that organic or inorganic flame retardants always have insurmountable shortcomings and deficiencies. Therefore, the research and development of comprehensive, safe, efficient, durable, environmentally friendly and economically reasonable composite flame retardants has become the core content of research in the field of flame retardants. At present, there are two main research directions for composite flame retardants. One is the expansion flame retardant represented by phosphorus-nitrogen flame retardant, which can form a dense porous foam carbon layer on the surface of the material when heated, which can not only prevent the further degradation of the inner polymer and the release of combustibles to the surface, but also prevent the transfer of heat source to the polymer and isolate oxygen, thereby effectively preventing the spread and propagation of flames and achieving a flame retardant effect. The other is the emerging new environmentally friendly flame retardant represented by phosphorus-monohydrate, which is halogen-free, low-smoke and low-toxic. The research focus is on how to obtain a highly compatible and stable inorganic hydrate structure that can be perfectly compounded with phosphorus-based flame retardants. Among the many inorganic hydrate structures, the hydrotalcite structure shows excellent performance.
[0004] Hydrotalcite, also known as layered double hydroxides (LDHs), is a type of two-dimensional nanomaterial with a layered structure. It is also an anionic clay, consisting of negatively charged interlayer anions and positively charged main layers. Due to its excellent physical and chemical properties, such as low toxicity, thermodynamic stability, easy preparation and non-flammability, hydrotalcite has been widely used in the field of polymer flame retardancy. Its flame retardant principle is that the -OH on its surface and the CO3 2-After thermal decomposition, H2O and CO2 are generated, which effectively dilute the concentration of oxygen and combustible gases in the environment. At the same time, the laminate generates metal oxides under high temperature conditions and covers the surface of the polymer matrix to form a heat insulation layer. However, due to the van der Waals force between the hydrotalcite nanosheets and the inorganic properties of the hydrotalcite itself, it is very easy to accumulate in the polymer matrix, which has a negative impact on its flame retardant properties.
[0005] Based on this, we proposed a green halogen-free hydrotalcite-based flame retardant and a preparation method thereof, hoping to solve the shortcomings of the existing technology. Summary of the invention
[0006] The purpose of the present invention is to provide a green halogen-free hydrotalcite-based flame retardant and a preparation method thereof in view of the existing problems.
[0007] The present invention is achieved through the following technical solutions:
[0008] A method for preparing a green halogen-free hydrotalcite-based flame retardant comprises the following steps:
[0009] S1. Add γ-chloropropyltriethoxysilane to an isopropanol solution, disperse it evenly by ultrasonication, grind and mix graphene and diatomaceous earth in a mass ratio of 1:10-20, add the mixture to the dispersion, stir at a constant temperature for 3-5 hours, filter, wash with deionized water for 3-5 times, and vacuum dry to constant weight to obtain a preliminary modified composite material for use;
[0010] S2, disperse the preliminary modified composite material into deionized water, and after ultrasonic dispersion, adjust the pH to 9-11 with NaOH, then heat it to 60-90°C, add the treatment agent to the dispersion, stir and react at constant temperature for 2-3h, filter, wash with water to neutrality, and then vacuum dry to constant weight to obtain the modified composite material for use;
[0011] S3. Adjust the pH to 9-11 with NaOH, add Al(NO3)3·9H2O and Mg(NO3)2·6H2O to deionized water at a molar ratio of 1:2-3, and perform ultrasonic treatment to obtain a salt solution; add NaOH and Na2CO3 to deionized water at a mass ratio of 1:0.8-0.9, and perform ultrasonic treatment to obtain an alkaline solution; add the modified composite material and deionized water at a mass volume ratio of 1g:100-150mL into a three-necked flask, and at room temperature, the salt solution and the alkaline solution are stirred at 3-5mL·min -1 After the addition is completed, let it stand at 60-70℃ for 6-8h, cool to room temperature, filter, wash with deionized water until neutral, and then vacuum dry to constant weight.
[0012] Further preferably, the volume ratio of γ-chloropropyltriethoxysilane to isopropanol solution in step S1 is 1:90-100.
[0013] More preferably, the grinding speed during the grinding and mixing in step S1 is 2000-4000 rpm, and the grinding time is 20-28 min.
[0014] Further preferably, the weight volume ratio of the graphene and diatomaceous earth grinding mixture to the dispersion liquid in step S1 is 1 g:90-95 mL.
[0015] Further preferably, during the constant temperature stirring in step S1, the stirring speed is controlled to be 200-300 rpm and the temperature is controlled to be 90-100°C.
[0016] Further preferably, the weight volume ratio of the preliminary modified composite material and deionized water described in step S2 is 1 g: 30-50 mL;
[0017] Further preferably, the components and corresponding percentages in the treatment agent described in step S2 are: 4-8% 3-chloro-2-hydroxypropyltrimethylammonium chloride, 3-4% polyethylene glycol, 6-10% soy lecithin, 0.7-0.9% glyphosate, and the remainder is deionized water.
[0018] More preferably, during the dropping process in step S3, the pH value in the three-necked flask is maintained at 9-11.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] The present invention provides a green halogen-free hydrotalcite-based flame retardant and a preparation method thereof. The hydrotalcite is used as the basis, and a modified composite material is added during the preparation process of the hydrotalcite. The addition of the composite material can effectively improve the dispersibility of the hydrotalcite, prevent the occurrence of agglomeration, and can be evenly dispersed in a polymer compound to improve the flame retardancy of the polymer compound. In addition, a quaternary ammonium long chain is introduced into the flame retardant of the present invention, so that the water resistance is better and the flame retardancy is further improved. Due to the porous structure, the flame retardant can also absorb the smoke and toxic acidic gas generated by combustion while being flame retardant, and play a role in purifying the air, and has good flame retardancy and smoke suppression performance. DETAILED DESCRIPTION
[0021] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Example 1
[0023] A method for preparing a green halogen-free hydrotalcite-based flame retardant comprises the following steps:
[0024] S1. After uniformly dispersing γ-chloropropyltriethoxysilane and isopropanol solution by ultrasonic dispersion at a volume ratio of 1:90, grind graphene and diatomaceous earth at a mass ratio of 1:10 at 2000 rpm for 20 min, add the mixture to the dispersion, stir at 200 rpm and 90° C. for 3 h, filter, wash with deionized water 3 times, and vacuum dry to constant weight to obtain a preliminary modified composite material for standby use;
[0025] The weight-to-volume ratio of the graphene and diatomaceous earth grinding mixture to the dispersion is 1 g:90 mL;
[0026] S2, the preliminary modified composite material and deionized water are dispersed in deionized water at a weight volume ratio of 1g:30mL, and after ultrasonic dispersion, the pH is adjusted to 9 with NaOH, and then the temperature is raised to 60°C, and the treatment agent is added to the dispersion. After constant temperature stirring and reaction for 2h, it is filtered, washed with water to neutrality, and then vacuum dried to constant weight to obtain the modified composite material for standby use;
[0027] The components and corresponding percentages in the treatment agent are: 4% of 3-chloro-2-hydroxypropyltrimethylammonium chloride, 3% of polyethylene glycol, 6% of soybean lecithin, 0.7% of glyphosate, and the balance is deionized water.
[0028] S3. Adjust the pH to 9 with NaOH, add Al(NO3)3·9H2O and Mg(NO3)2·6H2O to deionized water at a molar ratio of 1:2, and perform ultrasonic treatment to obtain a salt solution; add NaOH and Na2CO3 to deionized water at a mass ratio of 1:0.8, and perform ultrasonic treatment to obtain an alkaline solution; add the modified composite material and deionized water at a mass volume ratio of 1g:100mL into a three-necked flask, and at room temperature, the salt solution and the alkaline solution are stirred at 3mL·min -1 The mixture was added dropwise into a three-necked flask at a speed of 9. The pH value in the flask was maintained at 9 during the addition. After the addition was completed, it was allowed to stand at 60°C for 6 hours, cooled to room temperature, filtered, washed with deionized water until neutral, and then vacuum dried to constant weight.
[0029] Example 2
[0030] A method for preparing a green halogen-free hydrotalcite-based flame retardant comprises the following steps:
[0031] S1. After uniformly dispersing γ-chloropropyltriethoxysilane and isopropanol solution by ultrasonic method at a volume ratio of 1:95, grind graphene and diatomaceous earth at a mass ratio of 1:15 at 3000 rpm for 24 min, add the mixture to the dispersion, stir at 250 rpm and 95° C. for 4 h, filter, wash with deionized water 4 times, and vacuum dry to constant weight to obtain a preliminary modified composite material for standby use;
[0032] The weight-to-volume ratio of the graphene and diatomaceous earth grinding mixture to the dispersion is 1 g:92 mL;
[0033] S2, the preliminary modified composite material and deionized water are dispersed in deionized water at a weight volume ratio of 1g:40mL, and after ultrasonic dispersion, the pH is adjusted to 10 with NaOH, and then the temperature is raised to 75°C, and the treatment agent is added to the dispersion. After constant temperature stirring and reaction for 2.5h, it is filtered, washed with water to neutrality, and then vacuum dried to constant weight to obtain the modified composite material for standby use;
[0034] The components and corresponding percentages in the treatment agent are: 6% of 3-chloro-2-hydroxypropyltrimethylammonium chloride, 3.5% of polyethylene glycol, 8% of soybean lecithin, 0.8% of glycerophosphoric acid, and the balance is deionized water.
[0035] S3. Adjust the pH to 10 with NaOH, add Al(NO3)3·9H2O and Mg(NO3)2·6H2O to deionized water at a molar ratio of 1:2.5, and perform ultrasonic treatment to obtain a salt solution; add NaOH and Na2CO3 to deionized water at a mass ratio of 1:0.85, and perform ultrasonic treatment to obtain an alkaline solution; add the modified composite material and deionized water at a mass volume ratio of 1g:125mL into a three-necked flask, and at room temperature, vortex the salt solution and the alkaline solution at 4mL·min -1 The mixture was added dropwise into a three-necked flask at a speed of 10. The pH value in the flask was maintained at 10 during the addition. After the addition was completed, it was allowed to stand at 65°C for 7 hours, cooled to room temperature, filtered, washed with deionized water until neutral, and then vacuum dried to constant weight.
[0036] Example 3
[0037] A method for preparing a green halogen-free hydrotalcite-based flame retardant comprises the following steps:
[0038] S1. After uniformly dispersing γ-chloropropyltriethoxysilane and isopropanol solution by ultrasonic dispersion at a volume ratio of 1:100, grind graphene and diatomaceous earth at a mass ratio of 1:20 at 4000 rpm for 28 min, add the mixture to the dispersion, stir at 300 rpm and 100° C. for 5 h, filter, wash with deionized water 5 times, and vacuum dry to constant weight to obtain a preliminary modified composite material for standby use;
[0039] The weight volume ratio of the graphene and diatomaceous earth grinding mixture to the dispersion is 1g:95mL;
[0040] S2, the preliminary modified composite material and deionized water are dispersed in deionized water at a weight volume ratio of 1g:50mL, and after ultrasonic dispersion, the pH is adjusted to 11 with NaOH, and then the temperature is raised to 90°C, and the treatment agent is added to the dispersion. After constant temperature stirring and reaction for 3h, it is filtered, washed with water to neutrality, and then vacuum dried to constant weight to obtain the modified composite material for standby use;
[0041] The components and corresponding percentages in the treatment agent are: 8% of 3-chloro-2-hydroxypropyltrimethylammonium chloride, 4% of polyethylene glycol, 10% of soybean lecithin, 0.9% of glyphosate, and the balance is deionized water.
[0042] S3. Adjust the pH to 11 with NaOH, add Al(NO3)3·9H2O and Mg(NO3)2·6H2O to deionized water at a molar ratio of 1:3, and perform ultrasonic treatment to obtain a salt solution; add NaOH and Na2CO3 to deionized water at a mass ratio of 1:0.9, and perform ultrasonic treatment to obtain an alkaline solution; add the modified composite material and deionized water at a mass volume ratio of 1g:150mL into a three-necked flask, and at room temperature, simmer the salt solution and the alkaline solution at 5mL·min -1 The mixture was added dropwise into a three-necked flask at a speed of 100 μg / ml. During the addition, the pH value in the three-necked flask was maintained at 11. After the addition was completed, it was allowed to stand at 70°C for 8 hours, cooled to room temperature, filtered, washed with deionized water until neutral, and then vacuum dried to constant weight.
[0043] Comparative Example 1
[0044] A method for preparing a green halogen-free hydrotalcite-based flame retardant comprises the following steps:
[0045] S1. After γ-chloropropyltriethoxysilane and isopropanol solution are uniformly dispersed by ultrasonication at a volume ratio of 1:95, diatomaceous earth is ground at 3000 rpm for 24 min, added to the dispersion, stirred at 250 rpm and 95° C. for 4 h, filtered, washed with deionized water 4 times, and vacuum dried to constant weight to obtain preliminary modified diatomaceous earth for use;
[0046] The weight-to-volume ratio of the diatomaceous earth ground material to the dispersion is 1 g:92 mL;
[0047] S2, the preliminary modified diatomite and deionized water were dispersed in deionized water at a weight volume ratio of 1g:40mL, and after ultrasonic dispersion, the pH was adjusted to 10 with NaOH, and then the temperature was raised to 75°C, and the treatment agent was added to the dispersion. After stirring at a constant temperature for 2.5h, it was filtered, washed with water until neutral, and then vacuum dried to constant weight to obtain the modified diatomite for standby use;
[0048] The components and corresponding percentages in the treatment agent are: 6% of 3-chloro-2-hydroxypropyltrimethylammonium chloride, 3.5% of polyethylene glycol, 8% of soybean lecithin, 0.8% of glyphosate, and the balance is deionized water.
[0049] S3. Adjust the pH to 10 with NaOH, add Al(NO3)3·9H2O and Mg(NO3)2·6H2O to deionized water at a molar ratio of 1:2.5, and perform ultrasonic treatment to obtain a salt solution; add NaOH and Na2CO3 to deionized water at a mass ratio of 1:0.85, and perform ultrasonic treatment to obtain an alkaline solution; add modified diatomaceous earth and deionized water at a mass volume ratio of 1g:125mL into a three-necked flask, and simmer the salt solution and alkaline solution at room temperature at 4mL·min -1 The mixture was added dropwise into a three-necked flask at a speed of 10. The pH value in the flask was maintained at 10 during the addition. After the addition was completed, it was allowed to stand at 65°C for 7 hours, cooled to room temperature, filtered, washed with deionized water until neutral, and then vacuum dried to constant weight.
[0050] Comparative Example 2
[0051] A method for preparing a green halogen-free hydrotalcite-based flame retardant comprises the following steps:
[0052] S1. After uniformly dispersing γ-chloropropyltriethoxysilane and isopropanol solution by ultrasonic method at a volume ratio of 1:95, grind graphene and diatomaceous earth at a mass ratio of 1:15 at 3000 rpm for 24 min, add the mixture to the dispersion, stir at 250 rpm and 95° C. for 4 h, filter, wash with deionized water 4 times, and vacuum dry to constant weight to obtain a modified composite material for standby use;
[0053] The weight-to-volume ratio of the graphene and diatomaceous earth grinding mixture to the dispersion is 1 g:92 mL;
[0054] S2. Adjust the pH to 10 with NaOH, add Al(NO3)3·9H2O and Mg(NO3)2·6H2O to deionized water at a molar ratio of 1:2.5, and perform ultrasonic treatment to obtain a salt solution; add NaOH and Na2CO3 to deionized water at a mass ratio of 1:0.85, and perform ultrasonic treatment to obtain an alkaline solution; add the modified composite material and deionized water at a mass volume ratio of 1g:125mL into a three-necked flask, and at room temperature, vortex the salt solution and the alkaline solution at 4mL·min -1 The mixture was added dropwise into a three-necked flask at a speed of 10. The pH value in the flask was maintained at 10 during the addition. After the addition was completed, it was allowed to stand at 65°C for 7 hours, cooled to room temperature, filtered, washed with deionized water until neutral, and then vacuum dried to constant weight.
[0055] Comparative Example 3
[0056] A method for preparing a green halogen-free hydrotalcite-based flame retardant comprises the following steps:
[0057] The pH value was adjusted to 10 with NaOH, Al(NO3)3·9H2O and Mg(NO3)2·6H2O were added to deionized water at a molar ratio of 1:2.5, and ultrasonic treatment was performed to obtain a salt solution; NaOH and Na2CO3 were added to deionized water at a mass ratio of 1:0.85, and ultrasonic treatment was performed to obtain an alkaline solution; diatomaceous earth and deionized water were added to a three-necked flask at a mass volume ratio of 1 g:125 mL, and the salt solution and the alkaline solution were stirred at room temperature at 4 mL min -1 The mixture was added dropwise into a three-necked flask at a speed of 10. The pH value in the flask was maintained at 10 during the addition. After the addition was completed, it was allowed to stand at 65°C for 7 hours, cooled to room temperature, filtered, washed with deionized water until neutral, and then vacuum dried to constant weight.
[0058] Performance Test:
[0059] The methods of the above-mentioned Examples 1 to 3 and Comparative Examples 1 to 3 were respectively used to prepare polypropylene / hydrotalcite-based composite materials, and polypropylene (PP) and the prepared flame retardant were mixed in a mass ratio of 96:4, added to a twin-screw extruder, extruded and granulated to prepare a composite material of PP and a flame retardant, which were respectively recorded as Examples 1 to 3 and Comparative Examples 1 to 3, and then the flame retardant properties of each group of samples were tested according to the corresponding national standards and sizes.
[0060] The limiting oxygen index (LOI) of the sample was determined using an HC-2 oxygen index meter. Test conditions: The sample was tested according to GB / T 2406.2-2009 standard. The sample size was 80×10×4mm. 3 .
[0061] The vertical combustion level (UL-94) of the sample was tested using a CZF-3 horizontal vertical combustion tester. Test conditions: The sample was tested according to GB / T2408 standard. The sample size was 130×13×4mm. 3 Each group of samples was tested 3 times and the average value was taken.
[0062] The test results are shown in Table 1 below:
[0063] Table 1
[0064] UL-94 LOI / % Example 1 V-1 31.2 Example 2 V-1 31.5 Example 3 V-1 29.8 Comparative Example 1 V-1 25.6 Comparative Example 2 V-2 24.3 Comparative Example 3 V-2 20.2
[0065] It can be seen from Table 1 above that compared with the comparative example, the flame retardant prepared in the embodiment of the present invention is conducive to improving the UL-94 flame retardancy rating, and its limiting oxygen index LOI value is also greatly improved, and the effect is significantly better than that of the control group, indicating that the modified composite material of the present invention can cooperate with the hydrotalcite, can significantly improve the compatibility between the hydrotalcite and the polymer, and can further improve the flame retardancy of the hydrotalcite.
[0066] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a green halogen-free hydrotalcite-based flame retardant, characterized in that: The steps include: S1. Add γ-chloropropyltriethoxysilane to an isopropanol solution, disperse it evenly by ultrasonication, grind and mix graphene and diatomaceous earth in a mass ratio of 1:10-20, add the mixture to the dispersion, stir at a constant temperature for 3-5 hours, filter, wash with deionized water for 3-5 times, and vacuum dry to constant weight to obtain a preliminary modified composite material for use; S2, disperse the preliminary modified composite material into deionized water, and after ultrasonic dispersion, adjust the pH to 9-11 with NaOH, then heat it to 60-90°C, add the treatment agent to the dispersion, stir and react at constant temperature for 2-3h, filter, wash with water to neutrality, and then vacuum dry to constant weight to obtain the modified composite material for use; S3. Adjust the pH to 9-11 with NaOH, add Al(NO3)3·9H2O and Mg(NO3)2·6H2O to deionized water at a molar ratio of 1:2-3, and perform ultrasonic treatment to obtain a salt solution; add NaOH and Na2CO3 to deionized water at a mass ratio of 1:0.8-0.9, and perform ultrasonic treatment to obtain an alkaline solution; add the modified composite material and deionized water at a mass volume ratio of 1g:100-150mL into a three-necked flask, and at room temperature, the salt solution and the alkaline solution are stirred at 3-5mL·min -1 After the addition is completed, let it stand at 60-70℃ for 6-8h, cool to room temperature, filter, wash with deionized water until neutral, and then vacuum dry to constant weight.
2. The method for preparing a green halogen-free hydrotalcite-based flame retardant according to claim 1, characterized in that: The volume ratio of γ-chloropropyltriethoxysilane to the isopropanol solution in step S1 is 1:90-100.
3. The method for preparing a green halogen-free hydrotalcite-based flame retardant according to claim 1, characterized in that: The grinding speed during the grinding and mixing in step S1 is 2000-4000 rpm, and the grinding time is 20-28 min.
4. The method for preparing a green halogen-free hydrotalcite-based flame retardant according to claim 1, characterized in that: The weight volume ratio of the graphene and diatomaceous earth grinding mixture to the dispersion liquid described in step S1 is 1 g:90-95 mL.
5. The method for preparing a green halogen-free hydrotalcite-based flame retardant according to claim 1, characterized in that: During the constant temperature stirring in step S1, the stirring speed is controlled to be 200-300 rpm and the temperature is controlled to be 90-100°C.
6. The method for preparing a green halogen-free hydrotalcite-based flame retardant according to claim 1, characterized in that: The weight volume ratio of the preliminary modified composite material described in step S2 to deionized water is 1 g:30-50 mL.
7. The method for preparing a green halogen-free hydrotalcite-based flame retardant according to claim 1, characterized in that: The components and corresponding percentages of the treatment agent described in step S2 are: 4-8% 3-chloro-2-hydroxypropyltrimethylammonium chloride, 3-4% polyethylene glycol, 6-10% soybean lecithin, 0.7-0.9% glycerophosphoric acid, and the balance is deionized water.
8. The method for preparing a green halogen-free hydrotalcite-based flame retardant according to claim 1, characterized in that: During the dropping process described in step S3, the pH value in the three-necked flask is maintained at 9-11.
9. A green halogen-free hydrotalcite-based flame retardant prepared by the method according to any one of claims 1 to 8.